Magnetic Field-Sensitive Radical Pair Dynamics in Polymethylene Ether-Bridged Donor–Acceptor Systems - Hoang, Hao Minh (ACS Omega, 2018)
[Image: see text] Donor–acceptor systems forming exciplexes are versatile models for the study of magnetic field effects (MFEs) on charge recombination reactions. The MFEs originate from singlet–triplet interconversion within transient radical ion pairs (RIPs), which exist in a dynamic equilibrium with the exciplexes. Here, we describe the synthesis and MFEs of the chain-linked N,N-dimethylaniline (DMA)/9-methylanthracene (MAnt) donor–acceptor system MAnt–(CH(2))(n)–O–CH(2)–CH(2)–DMA for n = 6, 8, 10, and 16. The MFEs are found to increase with increasing chain length. Effects as large as 37.5% have been observed for the long-chain compound with n = 16. The solvent dependence of the MFEs at magnetic field intensity 75 mT is reported. For the range of solvent static dielectric constants ε(s) = 6.0–36.0, the MFEs go through a maximum for intermediate polarities, for which the direct formation of RIPs prevails and their dissociation and reencounter are balanced. Field-resolved measurements (MARY spectra) are reported for solutions in butyronitrile. The MARY spectra reveal that for n = 8, 10, 16, the average exchange interaction is negligible during the coherent lifetime of the radical pair. However, singlet–triplet dephasing broadens the lineshape; the shorter the linker, the more pronounced this effect is. For n = 6, a dip in the fluorescence intensity reveals a nonzero average exchange coupling of the order of ±5 mT. We discuss the field-dependence in the framework of the semiclassical theory taking spin-selective recombination, singlet–triplet dephasing, and exchange coupling into account. Singlet recombination rates of the order of 0.1 ns(–1) and various degrees of singlet–triplet dephasing govern the spin dynamics. In addition, because of a small free energy gap between the exciplex and the locally excited fluorophore quencher pair, a fully reversible interconversion between the RIP, exciplex, and locally excited fluorophore is revealed by spectrally resolved MFE measurements for the long-chain systems (n = 10, 16).